Analisis Resiko Kurikulum Merdeka Belajar Dengan Menggunakan Metode Failure Mode and Effect Analysis (FMEA) Pada Tingkat Sekolah Dasar - Maya Nurfitriyanti; Burju Ruth; Henny Suharyati (Kelola: Jurnal Manajemen Pendidikan, 2024)
This study aims to analyze the risks associated with the implementation of the Merdeka Belajar curriculum at the elementary school level using the FMEA method. This research is a literature study employing a qualitative approach, followed by the FMEA method to conduct a risk analysis of the issues in implementing the Merdeka Belajar curriculum at the elementary school level. The findings indicate several levels of issues and corresponding solutions for the implementation of the Merdeka Belajar curriculum, including:1) Teachers' lack of ability to develop learning models, evaluation methods, and learning tools. This issue can be addressed by involving teachers in training and workshops to enhance their skills in creating effective learning models and tools to improve classroom teaching, 2) Insufficient teacher understanding of the Merdeka Belajar curriculum implementation. This can be resolved by enrolling teachers in training programs focused on implementing learning with the Merdeka Belajar curriculum, 3) Limited teacher ability to understand diverse students and student heterogeneity. This can be addressed by enhancing teachers' psychological skills to better understand their students, 4) Lack of understanding of information technology usage among teachers and staff, as well as limited internet access and infrastructure. Solutions include government support for the provision of learning facilities such as internet access and infrastructure. Additionally, schools can involve teachers and educators in workshops and training sessions on technology and information usage, 5) Suboptimal time management. This issue can be addressed by improving time management to effectively organize teaching activities using the Merdeka Belajar curriculum, 6) Lack of student competitiveness. This can be enhanced by motivating students to value the importance of striving for progress and success in their learning.